Pengajaran Bahasa Berbasis Tugas (Task-Based Language Teaching) Studi Kasus Guru Bahasa Inggris SMP - Hilhami Eka Dewi (PPG IKIP Siliwangi, 2023)
Like many methodological innovations, Task-Based Language Teaching (TBLT) has been applied to many English curricula throughout Asia. However, little research has been conducted to explore what teachers know and believe about these method reforms in the specific context of their profession. This research originates from an in-depth study of teacher cognition in Junior High Schools in Tebo District, Indonesia using multi-methods of data collection. In this study, the findings will be reviewed and explained from one of the methods used to obtain teacher knowledge and attitudes towards narrative inquiry. In detail, teachers were asked to write reflective comments in Indonesian about their attitudes towards TBLT, and the experiences they had after implementing TBLT in class. After explaining some of the findings, the approach to data collection and the relevant context can be used as a reference for further research.